STRATEGI DIGITAL CSR UNTUK MENINGKATKAN LOYALITAS MEREK DAN KEPUTUSAN PEMBELIAN: PERSPEKTIF TEORI PERTUKARAN SOSIAL DAN GENERASI Y - Rinaldi Bursan (Yayasan Nusantara Hasana Berdikari, 2025)
Digital transformation has changed the way companies establish relationships with consumers, including in communicating social responsibility activities through Digital Corporate Social Responsibility (DSR) strategies. This study aims to analyze the effect of DSR on brand loyalty and purchase intentions of Generation Y consumers in Indonesia, using the Social Exchange Theory approach. Data were collected from 385 Generation Y respondents who actively use social media and have been exposed to digital CSR activities, using a 5-point Likert scale questionnaire. The analysis method used is Partial Least Squares - Structural Equation Modeling (PLS-SEM) through SmartPLS. The results of the study indicate that DSR has a significant effect on brand loyalty and purchase intentions. Brand loyalty is also proven to mediate the relationship between DSR and purchase intentions. These findings indicate that DSR not only has a reputational impact, but also contributes to shaping consumer loyalty and purchasing decisions. This study provides theoretical implications for the development of Social Exchange Theory in a digital context, as well as practical implications for companies in designing communication strategies based on social values. Further research is recommended to explore the moderating role of brand trust or perceived authenticity in the relationship between DSR and consumer behavior.